Sspp: Secure Scheme for Provenance Forgery and Packet Drop Detection in Wireless Sensor Network - Ujwala, N; Siddaramappa, V (International Journal of Computer Sciences and Engineering, 2025)
Deployment of sensor networks are used in many applications data that are collected by these sensors are used in decision making such as in Supervisory control and data Acquisition, Battlefield monitoring systems and in many other applications. Data are collected from multiple sources through intermediate nodes. Malicious adversary may introduce additional nodes in the network or compromise existing ones. So trustworthiness of the data collected from different sources is important for decision making. In evaluating the trustworthiness of the sensor data provenance plays a key factor. Several challenges that affect the provenance management include secure transmission and efficient storage, bandwidth consumption and low energy. A novel lightweight schema was proposed to transmit provenance of the sensor data securely. Bloom filters are used in the proposed technique to encode provenance. Efficient mechanisms are introduced for reconstruction of the base station and provenance verification. The secure provenance scheme was extended with the functionality to detect packet drop attacks done by malicious data forwarding nodes. We evaluate the proposed technique and the results prove the effectiveness and efficiency of the lightweight secure provenance scheme in detecting packet forgery and loss attacks.